Representatives of the National Literature Era - Hakary Qasm Baez (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
National Literature is the nationality of Turkish literature, which developed between 1908 and 1923 and began with the nationalism movements of the second legitimacy. This literary movement lasts until the Republican era.During this period, the concept of simplification in the language of Turkish literature was adopted.A closer understanding of the language of the people has been observed.These cases were also found in the works produced during this period.- The authors in the period fourth of national literature were also influenced by the works written by the authors in folk literature.Examples of the works of these authors have been added to their own works.The representatives of the National Literature period are Omer Seyfettin. (1884-1920), Ziya Gokalp.(1876-1924), Mehmet Emin YurdaKul. (1869-1944), Halide Edip Adivar. (1884-1964), Mehmet Fuat Kopruli (1890-1966), Refik Khalid Karay (1888-1965).